Technological interdependence and regional growth in Europe: Proximity and synergy in knowledge spillovers - Basile, Roberto; Capello, Roberta; Caragliu, Andrea (Papers in regional science, 2012)
The economic growth literature suggests that knowledge spillovers are subject to distance decay effects. In this paper the main aim is to provide a theoretical framework and empirical evidence on the role played by other kinds of proximities, namely relational, social and technological proximity, in explaining productivity growth. Using a sample of 249 EU 27 NUTS 2 regions in the period 1990–2004, semiparametric spatial autoregressive models are estimated. Results provide evidence of a positive role of social and relational proximities as important channels of knowledge spillovers, and on the fact that, when simultaneously present, different kinds of proximities generate synergic effects on growth. Resumen La literatura sobre el crecimiento económico sugiere que los spillovers de conocimiento están sujetos a efectos de deterioro por distancia. El objetivo principal de este artículo es proporcionar un marco teórico y pruebas empíricas sobre el papel desempeñado por otros tipos de proximidades (relacional, social y tecnológica), a la hora de explicar el crecimiento de la productividad. Utilizando una muestra de 249 regiones NUTS 2 de la UE 27 para el período 1990‐2004, se estiman modelos autorregresivos espaciales semiparamétricos. Los resultados aportan pruebas del papel positivo de las proximidades sociales y relacionales como canales importantes de spillovers de conocimientos, y del hecho de que, cuando se presentan simultáneamente, los diferentes tipos de proximidades generan efectos sinérgicos sobre el crecimiento.